Integration of Digital Literacy in Curriculum Management to Optimize Learning Quality in Elementary Schools - Yuni Tri Widya Ningrum; Dian Hidayati; Suyatno Suyatno (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: Adaptive and innovative curriculum management plays a central role in optimizing learning quality in the digital era. This study aims to describe the implementation of digital literacy integration within curriculum management in Elementary Schools, as well as to identify its challenges. Using a descriptive qualitative approach, this case study was conducted at SD Muhammadiyah Condongcatur. Informants were selected through purposive sampling, consisting of the vice head of curriculum, digital literacy coordinator, and class teachers. Data was collected through in-depth interviews, participatory observation, and document analysis, then thematically analyzed. The research findings show that digital literacy integration is implemented comprehensively across every aspect of curriculum management: planning, organizing, implementation, and evaluation. This proactive implementation positively correlates with an increase in learning quality, characterized by students who are more literate in information, media, and technology, as well as more interactive learning. Nevertheless, the main challenges found are the need for continuous technology adaptation for teachers and infrastructure constraints. This study concludes that an adaptive curriculum management strategy for digital literacy is proven to be effective, but requires holistic support from human resources and facilities. Keywords: integration; digital literacy; curriculum management; learning quality